Caracterización de residuos sólidos urbanos en el cantón Patate provincia de Tungurahua - Moreira Aguiar, David Alexander (2025)
This study presents a comprehensive analysis of urban solid waste in Patate Canton located in Tungurahua Province – Ecuador. The study used the methodology proposed by Arellano et al. (2024) identified as Interdisciplinary Approach for the Sustainable Management of Drinking Water and Solid Waste in Ecuador. The study area encompassed 63 residential blocks, stratified into three socioeconomic groups: stratum B (23.81%) with above-average income, stratum C (73.02%) with average income, and stratum D (3.17%) representing lower-income households. A stratified random sampling approach was employed, involving 77 households proportionally selected from each stratum, with waste collected over a seven-day period. Per capita waste generation (PCP) was calculated as 0.48 kg/inhabitant/day for stratum B, 0.43 kg/inhabitant/day for stratum C, and 0.40 kg/inhabitant/day for stratum D, yielding a weighted average of 0.44 kg/inhabitant/day. Statistical analysis included box-and-whisker plots for outlier detection and an ANOVA with Tukey’s post hoc test, which confirmed statistically significant differences in waste generation among the strata. In terms of physical composition, organic waste was the dominant category, comprising 63.47% of the total, followed by potentially recyclable materials (27.24%), materials with future recycling potential (0.15%), and non-recyclable waste (9.10%) destined for landfill disposal. The average loose density of waste was estimated at 197.87 kg/m³. These findings offer essential, up-to-date data on urban waste generation and composition in Patate and serve as a technical foundation for developing integrated solid waste management systems that reflect the locality’s socioeconomic and environmental conditions.